THE TEACHERS' CLINIC. - Kaulback, Frank S.; Gustafson, George A. (The Accounting Review, 1952)
Abstract The accountant's main task consists of the periodic determination of the revenue, costs, income and financial status of the business enterprise. In this connection, accounting has been defined as the art of recording, classifying, summarizing and interpreting. The statement accounting for variation in net profit is usually one of the rough spots encountered in intermediate accounting and the particular difficulty lies in the analysis of the factors causing the change in gross profit. Members of the Committee on Visual Aids are currently available to render assistance, upon request, to individual teachers of accounting. Highly effective use of visual aids has been made particularly in such courses of the accounting curriculum as cost accounting, auditing, elementary and advanced accounting theory, accounting reports, the analysis of financial statements and Certified Public Accountant problem review. Teachers of accounting are urged to call upon the membership of tile Committee on Visual Aids for any assistance desired in connection with attempts to develop visual aids applications or in resolving problems encountered.